Amyloid precursor protein in peripheral granulocytes as a potential biomarker for Alzheimer's disease - Xiaonan Wang; Xihai Li; Jie Yang; Ming Yu; Jinmei Wu (Bangladesh Pharmacological Society, 2016)
The aim of this study was to assess the potential of amyloid precursor protein in peripheral granulocytes as a diagnostic biomarker for early detection of Alzheimer's disease. Immunohistochemistry and flow cytometry were used to evaluate amyloid precursor protein expression levels and subcellular localization in Alzheimer's disease. Much higher amyloid precursor protein expression was observed in some leukocytes from Alzheimer's disease patients, compared with samples from non-Alzheimer's disease controls. In addition, flow cytometry data indicated significantly higher amyloid precursor protein expression in granulocytes from Alzheimer's disease patients compared with control values. No statistically significant differences in amyloid precursor protein expression were obtained in lymphocytes or monocytes between the patient groups. In conclusion, amyloid precursor protein expression level in peripheral blood granulocyte is a potential biomarker for early diagnosis of Alzheimer's disease.